Orthogonal Fault Rupture and Rapid Postseismic Deformation Following 2019 Ridgecrest, California, Earthquake Sequence Revealed From Geodetic Observations. Issue 5 (10th March 2020) - Feng, Wanpeng; Samsonov, Sergey; Qiu, Qiang; Wang, Yuqing; Zhang, Peizhen; Li, Tao; Zheng, Wenjun
Abstract: We studied the 2019 Mw 6.4 and Mw 7.1 Ridgecrest, California, earthquake sequence, using Sentinel‐1 and ALOS‐2 coseismic interferograms and subpixel offsets to retrieve the three‐dimensional (3‐D) surface displacements. By inverting the 3‐D displacements, optimal dip angles of the earthquake faults and the slip model were obtained. The interferometric synthetic aperture radar‐based slip model supplemented with the analysis of GPS data shows that the Mw 6.4 event ruptured two orthogonal faults and its major geodetic moment was released by sinistral motion on a NE‐SW trending fault that dips 78° NW. Right‐lateral slip on NW‐SE trending subvertical faults was responsible for the Mw 7.1 earthquake. Postseismic analysis with U.S. Geological Survey earthquake catalog and GPS time series at site P595 shows that the postseismic surface deformation following the Mw 7.1 event has similar temporal patterns with the postseismic moment release, but requires more energy. This implies that the early aftershocks were likely controlled by rapid afterslip following the mainshock. Key Points: The 3‐D surface displacements of the 2019 Ridgecrest earthquakes are derived from Sentinel‐1 and ALOS‐2 InSAR Orthogonal fault ruptures of the Mw 6.4 event are revealed by using GPS horizontal measurements The rapid decay of aftershocks is explained by the afterslip following the mainshocks